Drawn by the current - Green, Jocelyn (Green, Jocelyn. Windy City saga, 2022)
"A birthday excursion turns deadly when the SS Eastland capsizes with insurance agent Olive Pierce and her best friend on board. After her escape, Olive discovers her friend is among the missing victims. When she begins investigating the accident, more setbacks arise. Finding the truth will take all she's got to beat those who want to sabotage her progress"--